2009
DOI: 10.1248/bpb.32.1741
|View full text |Cite
|
Sign up to set email alerts
|

Processed Aconite Root Prevents Cold-Stress-Induced Hypothermia and Immuno-Suppression in Mice

Abstract: Processed aconite root (PA) is a crude drug used in traditional Chinese or Japanese medicine to generate heat in interior body and dispel cold. We evaluated the effects of PA on hypothermia and reduction in the activity of natural killer (NK) cells in mice exposed to chronic cold stress. Male mice were reared at 4°C, and powdered PA was administered for 10 d as a food additive. Core body temperature of mice significantly decreased by approximately 1°C after rearing in a cold environment, and PA administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Yang deficiency Syndrome indeed appeared in many emergency and serious diseases, including the late stage of AIDS. Processed aconite root (a Chinese medicine) was shown to prevent cold-stress-induced hypothermia and immunosuppression in mice [12]. Higenamine and its enantiomer, the active ingredients of aconite root, reduced iNOS expression and NO production, suppressed inflammatory reactions, and increased survival rates in LPS-treated mice [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Yang deficiency Syndrome indeed appeared in many emergency and serious diseases, including the late stage of AIDS. Processed aconite root (a Chinese medicine) was shown to prevent cold-stress-induced hypothermia and immunosuppression in mice [12]. Higenamine and its enantiomer, the active ingredients of aconite root, reduced iNOS expression and NO production, suppressed inflammatory reactions, and increased survival rates in LPS-treated mice [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first evidence that adjunctive berberine or metformin treatment significantly prevents olanzapine-induced brown fat weight loss. The weight of rodent brown fat is shown to be associated with changes in core body temperature [50]. Our tissue weight data strongly suggest the mechanism of action for metformin or berberine occurs by increasing energy expenditure or directly reducing energy storage, rather than inhibition of energy intake.…”
Section: Discussionmentioning
confidence: 60%
“…[49] Core BT in untreated mice was significantly decreased by about 1°C by day 5 of the cold exposure when compared with mice maintained at normal room temperature (24°C). However, in mice receiving Acn added to a standard murine powdered chow available ad libitum , the BT reduction was significantly counteracted in a dose-dependent manner (0.063, 0.25 and 1.0 g/kg/day were tested) such that there was no significant difference for any dose on any treatment day from the normal mice (the Acn 1.0 g dose actually showed significantly higher BT than normal controls on days 5, 7 and 9 after cold initiation).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that the mice were kept in dark at night and with lights on during the day, the study was most likely carried out in the morning (e.g., between 08:00 and 12:00 hours or 02–06 HALO). In the study by Makino et al .,[49] they reported that the mice were housed under a 12-hour L–12 hour D schedule with L-on from 07:00 to 19:00 hours and BT was measured between 13:00 and 15:00 hours, which would be in the middle of the daily resting span (06–09 HALO). Both of these studies were thus carried out at only one of the six different circadian times that we used in our study in order to consider the well-known circadian variation in mouse body temperature (i.e., BT reaches its minima during mid-L and maxima during mid-D).…”
Section: Discussionmentioning
confidence: 99%